A comprehensive review of high-performance photoacoustic microscopy systems - Eunwoo Park; Donggyu Kim; Mingyu Ha; Donghyun Kim; Chulhong Kim (Photoacoustics)
Photoacoustic microscopy (PAM), an imaging modality with emerging importance in diverse biomedical applications, provides excellent structural and functional information at the micro-scale. Technological innovations have significantly enhanced PAM’s performance, including sensitivity and contrast, making it a powerful tool. This review explores high-performance PAM, focusing on its signal-to-noise ratio, imaging speed, resolution, depth, functionality, and practicality, and commenting on the role of artificial intelligence in enhancing each feature. After providing comprehensive insights, the review concludes with future directions for developing high-performance PAM for advanced biomedical imaging and clinical applications.